2009
DOI: 10.1002/mrm.21861
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐contrast magnetic resonance imaging measurements in intracranial aneurysms in vivo of flow patterns, velocity fields, and wall shear stress: Comparison with computational fluid dynamics

Abstract: Evolution of intracranial aneurysms is known to be related to hemodynamic forces such as wall shear stress (WSS) and maximum shear stress (MSS). Estimation of these parameters can be performed using numerical simulations with computational fluid dynamics (CFD), but can also be directly measured with magnetic resonance imaging (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(192 citation statements)
references
References 28 publications
7
180
1
4
Order By: Relevance
“…Such numerical simulations permit the detailed analysis of local flow patterns and calculation of additional relevant parameters such as pressure differences or wall shear rates. In recent studies, comparisons of invivo and in-vitro MRI data with results from CFD simulations demonstrated comparable agreement for global flow parameters and flow patterns (46,47). However, for assuming accurate in vivo flow patterns, WSS estimation is expected to be more accurate compared the MRI based on the inherently higher spatiotemporal resolution of meshed vascular geometries used for the numerical calculations.…”
Section: Discussionmentioning
confidence: 98%
“…Such numerical simulations permit the detailed analysis of local flow patterns and calculation of additional relevant parameters such as pressure differences or wall shear rates. In recent studies, comparisons of invivo and in-vitro MRI data with results from CFD simulations demonstrated comparable agreement for global flow parameters and flow patterns (46,47). However, for assuming accurate in vivo flow patterns, WSS estimation is expected to be more accurate compared the MRI based on the inherently higher spatiotemporal resolution of meshed vascular geometries used for the numerical calculations.…”
Section: Discussionmentioning
confidence: 98%
“…Phase contrast MRI (PC-MRI) suffers from data inconsistency, partial-volume effects (Tang et al, 1993), intravoxel phase dispersion and inadequate SNR at high spatial resolutions (Figure 8). PC-MRI is not currently capable of providing accurate absolute measurements of WSS (Boussel et al, 2009), and has been shown to underestimate blood flow velocities in the carotid bifurcation by 31-39% . As shown in section 3, spiral FVE produces accurate velocity histograms compared with those acquired with Doppler ultrasound.…”
Section: Wall Shear Rate Estimation Using Spiral Fvementioning
confidence: 99%
“…3D velocity vector field, as an independent flow variable from which all the other hemodynamic variables like wall shear stress can be calculated, may also be predicted using image-based patient-specific computational fluid dynamic (CFD) simulations (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in this area used PC MRI to analyze hemodynamics in intracranial arteries and aneurysms (3,4,6,8,(11)(12)(13)(14)(15) and aorta (16,17 …”
Section: Introductionmentioning
confidence: 99%